2003
DOI: 10.1038/sj.embor.7400033
|View full text |Cite
|
Sign up to set email alerts
|

Fibulins: physiological and disease perspectives

Abstract: The fibulins are a family of proteins that are associated with basement membranes and elastic extracellular matrix fibres. This review summarizes findings from studies of animal models of fibulin deficiency, human fibulin gene mutations, human tumours and injury models that have advanced our understanding of the normal and pathological roles of members of this formerly obscure family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
243
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(251 citation statements)
references
References 64 publications
6
243
0
2
Order By: Relevance
“…The targets of miR-197 are ACVR1 and TSPAN3 genes while EFEMP2 is the target of miR-346 [156]. The EFEMP2 gene is thought to have tumor suppressor functions while the ACVR1 and TSPAN3 genes are involved in the control of cell growth and metastatic potential, respectively [157][158][159]. In vitro studies related with these miRNAs showed that their overexpression induced significant cell proliferation whereas inhibition caused growth arrest in human thyroid carcinoma follicular cells [154,156].…”
Section: Micrornasmentioning
confidence: 99%
“…The targets of miR-197 are ACVR1 and TSPAN3 genes while EFEMP2 is the target of miR-346 [156]. The EFEMP2 gene is thought to have tumor suppressor functions while the ACVR1 and TSPAN3 genes are involved in the control of cell growth and metastatic potential, respectively [157][158][159]. In vitro studies related with these miRNAs showed that their overexpression induced significant cell proliferation whereas inhibition caused growth arrest in human thyroid carcinoma follicular cells [154,156].…”
Section: Micrornasmentioning
confidence: 99%
“…Fibulins are 50-200 kDa in size (Timpl et al, 2003) and have a series of calcium binding EGF-like domains followed by a carboxyterminal fibulin-like domain (Argraves et al, 2003). There are five members of the fibulin family.…”
Section: Fibulinsmentioning
confidence: 99%
“…Fibulins constitute a small family of five extracellular matrix proteins that share a distinctive carboxyl-terminal globular domain and a tandem array of calcium-binding epidermal growth factor-like modules (1,25). Fibulin-1 and fibulin-2 contain an additional domain of three anaphylatoxin modules preceding the calcium-binding epidermal growth factor-like repeats and therefore are larger than fibulin-3, -4, and -5, which have identical modular structures.…”
mentioning
confidence: 99%